The performance of serial correlation preliminary test estimators under asymmetry loss functions - Nakale, S. N.; Kleyn, J.; Arashi, M.; Bekker, A. (South African Statistical Journal, 2015)
The risk performances, under the symmetric squared error loss function, of the estimators of the regression coefficients after a preliminary test for serial correlation have been widely investigated in the literature. However, it is well known that the use of the symmetric loss functions is inappropriate in estimation problems where underestimation and overestimation have different consequences. We consider the Linear Exponential and Bounded Linear Exponential loss functions which allows for asymmetry. The risks of the estimators are derived and numerically evaluated by using simulations.